2022
DOI: 10.1371/journal.pone.0275797
|View full text |Cite
|
Sign up to set email alerts
|

Maturation-based Corrective Adjustment Procedures (Mat-CAPs) in youth swimming: Evidence for restricted age-group application in females

Abstract: Inter-individual differences in maturation-associated development can lead to variations in physical performance, resulting in performance (dis)advantages and maturation selection bias within youth sport systems. To address such bias and account for maturational differences, Maturation-based Corrective Adjustment Procedures (Mat-CAPs) could be beneficial. The present study aimed to: (1) determine maturity timing distributions in youth female swimming; (2) quantify the relationship between maturation status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For instance, increasing age could relate to specific, or a combination of processes, including changing or competing interests 15,37 ; participation and competitive structure within swimming 8 ; changed meaning/purpose of swimming involvement in older age groups 38 ; and changing social relationships (coach and peer dynamics). 37,39 More sex-related explanations could relate to perceived social norms and expectations 40 ; prioritisation of alternative activities (e.g., education) 41 ; changing body shape and performance regression, 42 all of which have been connected with dropout.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, increasing age could relate to specific, or a combination of processes, including changing or competing interests 15,37 ; participation and competitive structure within swimming 8 ; changed meaning/purpose of swimming involvement in older age groups 38 ; and changing social relationships (coach and peer dynamics). 37,39 More sex-related explanations could relate to perceived social norms and expectations 40 ; prioritisation of alternative activities (e.g., education) 41 ; changing body shape and performance regression, 42 all of which have been connected with dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques have been widely used in various studies for the purpose of categorizing maturity status in children and adolescents [ 4 , 6 , 10 , 11 ]. It is even used to verify interindividual differences in youth sports, especially during the transition to adolescence [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques have been widely used in various studies for the purpose of categorizing maturity status in children and adolescents [4,6,10,11]. However, to our knowledge, no studies have been found that have tested and identi ed other anthropometric indicators to predict maturity status in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%